Young People as Drivers or Inhibitors of the Sustainability Movement: The Case of Anti-Consumption - F. Ziesemer; A. Hüttel; I. Balderjahn (Journal of Consumer Policy, 2021)
As overconsumption has negative effects on ecological balance, social equality, and individual well-being, reducing consumption levels among the materially affluent is an emerging strategy for sustainable development. Today's youth form a crucial target group for intervening in unsustainable overconsumption habits and for setting the path and ideas on responsible living. This article explores young people's motivations for engaging in three behavioural patterns linked to anti-consumption (voluntary simplicity, collaborative consumption, and living within one's means) in relation to sustainability. Applying a qualitative approach, laddering interviews reveal the consequences and values behind the anti-consumption behaviours of young people of ages 14 to 24 according to a means-end chains analysis. The findings highlight potential for and the challenges involved in motivating young people to reduce material levels of consumption for the sake of sustainability. Related consumer policy tools from the fields of education and communication are identified. This article provides practical implications for policy makers, activists, and educators. Consumer policies may strengthen anti-consumption among young people by addressing individual benefits, enabling reflection on personal values, and referencing credible narratives. The presented insights can help give a voice to young consumers, who struggle to establish themselves as key players in shaping the future consumption regime.
Keywords: 650; Voluntary simplicity; Collaborative consumption; Sustainable consumption; Means-end chain analysis; Laddering interviews; Youth